DESCRIPTION OF THE LEVEL OF COMMUNITY KNOWLEDGE ABOUT THE USE OF COUGH DRUGS IN THE HAMLET OF KRAGAN, GRABAG, MAGELANG FEBRUARY 2022 - Hastuti, Dwi (PHARMANAJA : PHARMACEUTICAL JOURNAL OF UNAJA, 2023)
ABSTRACT Background: The prevalence of cough is 15% in children and 20% in adults. The knowledge obtained shows that respondents who have a good level of knowledge about cough medicine self- medication are 45% while people with a low level of knowledge are 15%. Objective: This study aims to describe the level of public knowledge about the use of cough medicine in Kragan Hamlet, Grabag, Magelang. Method: This research method is descriptive observational with data collection using purposive sampling. The population in this study is the community in Kragan Hamlet, Grabag, Magelang, aged 17-55 years, the data used is primary data collected with a questionnaire instrument. The data were analyzed by calculating the percentage value of correct answers in the questionnaire section, then the level of knowledge was categorized into good, sufficient, poor categories. Results: The results showed that the level of public knowledge about the use of cough medicine in the good category was 26 respondents (32%), 31 respondents (38%) sufficient and 24 respondents (29%). Conclusion: The conclusion in this study was that the majority of the community's level of knowledge about the use of cough medicine in Kragan Hamlet, Grabag, Magelang was categorized as sufficient.